Performance assessment of solar chimney power plants with the impacts of divergent and convergent chimney geometry - Cuce, Erdem; Saxena, Abhishek; Cuce, Pinar Mert; Sen, Harun; Guo, Shaopeng; Sudhakar, K. (Oxford University Press, 2021)
Influence of area ratio (AR) on main performance parameters of solar chimney power plants (SCPPs) is investigated through a justified 3D axisymmetric CFD model. Geometric characteristics of Manzanares pilot plant (MPP) are taken into consideration for the numerical model. AR is varied from 0.5 to 10 to cover both concave and convex (convergent and divergent) solar chimney designs. Following the accuracy verification of the CFD results and proving mesh-independent solution, main performance oriented parameters are assessed as a function of AR such as velocity, temperature and pressure distribution within MPP, temperature rise of air in collector, mass flow rate of air around the turbine area, dynamic pressure difference across the turbine, minimum static pressure in the entire plant, power output and system efficiency. The results reveal that AR plays a vital role in performance figures of MPP. Mass flow rate of air (⁠m˙m˙⁠) is found to be 1122.1 kg/s for the reference geometry (AR = 1), whereas it is 1629.1 kg/s for the optimum AR value of 4. System efficiency (η) is determined to be 0.29% for the reference case; however, it is enhanced to 0.83% for the AR of 4.1. MPP can generate 54.3 kW electrical power in its current design while it is possible to improve this figure to 168.5 kW with the optimal AR value.